Tourism: Tourist image of Penang / Tan Chuan See - Tan, Chuan See (1984)
This study aims to provide a vivid picture of tourism in Penang. underlying the whole study is the emphasis on the importance of the views of the tourists themselves as a valuable indicative feedback to the understanding of this industry. The whole study is divided into 6 Chapters. Chapter I will discuss the aim and objective of the study, methodology and difficulties encountered during the fieldwork. Chapter II presents a picture of the development of tourism in Malaysia and Penang as well as the functions of the bodies responsible for promoting this industry. A descriptive analysis of the results of the study will be presented in the following three chapters. Chapter III deals with the demographic characteristics of the 50 respondents in this study. Chapter IV touches on the trip characteristics, the type of trip undertaken, where these tourists obtain information prior to the visit, why they chose Penang, the length of study and the kinds of food favoured while in Penang. Chapter V analyses the tourist's attitude towards Penang. Tourists normally have certain stereotypes or images about their destination. Hence this chapter aims to see how these images are justified on arrival. Finally the conclusion analyses the major findings and implications of the study. It concludes by putting forward a few suggestions and recommendation.